2021
DOI: 10.1016/j.synbio.2021.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparative metagenomic analysis of the vaginal microbiome in healthy women

Abstract: The composition of these vaginal microbiome has a significant impact on women's health. However, few studies have characterized the vaginal microbiome of healthy Chinese women using metagenomic sequencing. Here, we carried out a comparative metagenomic analysis to survey taxonomic, functional levels, and microbial communities' genome content in healthy women's vaginal microbiome. Overall, we observed a total of 111 species, including all dominant vaginal Lactobacillus species, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Nevertheless, shotgun metagenomics and circularizing probes-based RNA (ciRNA) sequencing targeted approaches with species-level resolution can provide in-depth insights into cervicovaginal microbiome. A growing number studies have employed shotgun sequencing of the vaginal metagenome 41 , 81 84 , metatranscriptome 85 , 86 and ciRNA 87 , 88 . Liu et al 84 have observed a total of 111 species in vaginal microbiome of healthy Chinese women, including all dominant vaginal Lactobacillus species, such as L. iners , L. crispatus , L. gasseri , and L. jensenii .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, shotgun metagenomics and circularizing probes-based RNA (ciRNA) sequencing targeted approaches with species-level resolution can provide in-depth insights into cervicovaginal microbiome. A growing number studies have employed shotgun sequencing of the vaginal metagenome 41 , 81 84 , metatranscriptome 85 , 86 and ciRNA 87 , 88 . Liu et al 84 have observed a total of 111 species in vaginal microbiome of healthy Chinese women, including all dominant vaginal Lactobacillus species, such as L. iners , L. crispatus , L. gasseri , and L. jensenii .…”
Section: Discussionmentioning
confidence: 99%
“…A growing number studies have employed shotgun sequencing of the vaginal metagenome 41 , 81 84 , metatranscriptome 85 , 86 and ciRNA 87 , 88 . Liu et al 84 have observed a total of 111 species in vaginal microbiome of healthy Chinese women, including all dominant vaginal Lactobacillus species, such as L. iners , L. crispatus , L. gasseri , and L. jensenii . It has been reported that L. crispatus , L. iners and G. vaginalis were the top three species in both HPV16-positive and control groups 83 .…”
Section: Discussionmentioning
confidence: 99%
“…The vaginal microbiomes of reproductive-aged women typically consist mainly of Lactobacillus or diverse anaerobes including Gardnerella, Prevotella, Sneathia, Fannyhessea, Megasphaera, Dialister, Mobiluncus, Peptonophilus, Shuttleworthia, Parvimonas and other genera [11][12][13][14][15] . Lactobacilli contribute to vaginal health by producing lactic acid, which lowers vaginal pH and creates a less favorable environment for pathogenic bacteria, and by competing with pathogens for space 11 .…”
Section: Introductionmentioning
confidence: 99%
“…However, 16S rRNA amplicon sequencing has low species resolution and functional information of microorganisms cannot be directly obtained from sequence data. Since metagenomic shotgun sequencing is able to identify microbial categories with high resolution and characterize their biological functions (16,17), it has been wildly used in explaining the structure and function of the vaginal microbiome (18,19). It's no doubt that metagenomic shotgun sequencing is a better tool to study the mechanisms of vaginal microbiome involvement in pathogenesis of BV.…”
Section: Introductionmentioning
confidence: 99%